Comparison of laparoscopic hepatectomy and percutaneous radiofrequency ablation for the treatment of small hepatocellular carcinoma: a meta-analysis - Fei Liu; Ling Tan; Lan Luo; Jun-jiang Pan (BMC Surgery, 2024)
Abstract Aim The purpose of this study was to compare the long-term outcomes of laparoscopic hepatectomy (LH) and percutaneous radiofrequency ablation (PRFA) for the treatment of small hepatocellular carcinoma. Methods We systematically searched PubMed, Embase, Web of Science, and Medline from January 2000 to May 2022 for literature comparing the efficacy of LH and PRFA in the treatment of small hepatocellular carcinoma (largest tumour diameter ≤ 3 cm, number of intrahepatic tumours ≤3, or diameter of a single intrahepatic lesion ≤5 cm. ). We assessed overall survival (OS), recurrence-free survival (RFS), local recurrence and complication rates. Results A total of 1886 patients with small HCC were included in the 8 studies included in this study, of which 839 underwent LH and 1047 underwent PRAF. The results of the meta-analysis showed that the two groups had the same 3-year (HR: 0.99, 95% CI: 0.67 to 1.47) and 5-year (HR: 1.30, 95% CI: 0.90 to 1.87) OS rates, and the LH group had better 3-year (HR: 0.58, 95% CI: 0.49 to 0.68) and 5-year (HR: 0.56, 95% CI: 0.37 to 0.85) RFS rates. The LH group had a lower local recurrence rate (OR: 0.19, 95% CI: 0.12 to 0.32), but the PRFA group had a lower complication rate (OR: 2.49, 95% CI: 1.76 to 3.54). Conclusion There was no difference in OS between LH and PRFA in the treatment of small HCC. LH had a higher RFS rate and a lower local recurrence rate, but PRFA had a lower complication rate. In general, the long-term efficacy of LH in the treatment of small HCC is better than that of PRFA. Considering the advantages of less trauma and a low complication rate of PRFA, a large number of RCT studies are needed for further verification in the future.